The Effect of Experiential Marketing and Emotional Marketing on Customer Satisfaction - Muheril, M.; Asia, Nur Asia; Tamin, T. (Golden Ratio of Mapping Idea and Literature Format, 2024)
This study aims to determine the effect of Experiential Marketing and Emotional Marketing variables on Customer Satisfaction at Aqila Ramlan Tailor Textile Mamuju Sewing Business. The research method used quantitative methods with primary data using a questionnaire. Respondents in the study were all customers who made purchases of Aqila Ramlan Tailor Textile Mamuju Sewing Business; the sample used an accidental sampling technique with a sample size of 30 respondents. The formula in this study uses multiple linear regression, validity test, reliability test, multiple linear regression, t-test, and F test. This study's results indicate that experiential and emotional marketing positively and significantly affect customer satisfaction at Aqila Ramlan Tailor Textile Mamuju Sewing Business. Experiential Marketing and Emotional Marketing simultaneously impact substantially purchasing decisions at the Aqila Ramlan Tailor Textile Mamuju Sewing Business.